Culture and civilization contradictions, innovation and tradition processes in the present (Journal of Philosophy Culture and Political Science, 2018)
The article considers the questions of the infl uence of modern Kazakh people relations on traditional cultureand cultural heritage, as well as features of the culture development in the future. Focusing on innovations inculture, the treatment to cultural heritage, cultural diffusion, it is necessary to develop the achievements of theKazakh culture, implemented many years of experience of mankind.The traditional system is considered as a phenomenon describing the integrity, stability of the organism ofsociety, as well as the article analyses the contradictions of culture and civilization, the processes of tradition andinnovation.Changes and creativity in culture are the aspect of the development of society. Innovation is considered fromthe position of the update method culture, unity of tradition and innovation is seen as a universal characteristic ofeach culture.Key words: culture, civilization, innovation, tradition, the truth, custom, public relations, morality,innovation, value.